FEASIBILITY STUDY OF A NOVEL SLEEVE TYPE SWITCHING VALVE - Falkner, Johannes; Ploeckinger, Andreas; Winkler, Bernd; Scheidl, Rudolf (International Journal of Fluid Power, 2011)
Digital hydraulics became an area of high interest in the last years. Its success depends heavily on cheap and fast switching valves which also feature compact design, low leakage, low electrical current and power requirements, and easy integration into the hydraulic system. This paper presents a feasibility study of a novel magnetically actuated, two coil, bistable 3/2 way sleeve type seat valve. The applicability of the valve was analysed by analytical models, a prototypal design, by measurements of the prototype, and by CFD simulation of flow forces. The sleeve concept turned out to have several inherent problems: insufficient closing-capability due to pressure forces and a pressure dependent clamping of the sleeve; some leakage because of manufacturing tolerances of the contact surfaces, and a complex design with many precise and costly parts to obtain compactness.